Metabolic risk in drug-resistant tuberculosis: prevalence of type 2 diabetes and its association with disease severity - Mason, Amita; Khanduri, Rakhee; Ahmed, Sohaib; Gupta, Rahul Kumar; Kumar, Manoj; Jethani, Varuna; Khanduri, Sushant (International Journal of Research in Medical Sciences, 2026)
Background: Tuberculosis (TB), caused by Mycobacterium tuberculosis, remains a global health challenge, further complicated by the co-prevalence of Type 2 Diabetes Mellitus (T2DM), particularly in drug-resistant TB (DR-TB) cases. This dual burden worsens clinical severity, leads to poor treatment outcomes, and prolongs infectivity. This study assessed the prevalence of T2DM among DR-TB patients and evaluated clinical-radiological correlations, alongside the relationship between HbA1c and 7-point glucose profiles. Methods: A cross-sectional study of 104 microbiologically confirmed DR-TB patients. Diabetes was diagnosed using ADA criteria. Demographics, clinical features, radiology, HbA1c, and 7-point glucose profiles were analyzed. Results: T2DM prevalence was 41.3% in DR-TB patients, with significant associations found between T2DM, older age, and higher BMI. Radiological abnormalities included infiltrates (32.7% upper, 32.7% middle zones), consolidation (30.8%), and cavities (20.2%). No significant association was found between diabetes and radiographic extent (p> 0.05). HbA1c demonstrated a strong positive correlation with mean 7-point glucose values (r=0.579; p=0.03). Conclusions: T2DM is highly prevalent among DR-TB patients. Routine screening and integrated TB–diabetes care are essential. HbA1c remains reliable for diagnosis and monitoring even during active TB disease.